ANALISIS KELENGKAPAN PENGISIAN KARTU PENDERITA KUSTA OLEH PETUGAS KUSTA DI KOTA PEKALONGAN - Nivia Cemerlang Rinjani; Dharminto Dharminto; Farid Agushybana; Atik Mawarni (Jurnal Kesehatan Masyarakat (Undip), 2021)
Leprosy is a contagious disease which is a neglected disease or a case that is neglected because it cannot be completely controlled. Based on PMK No.11 of 2019 concerning Leprosy Eradication, recording and reporting is one of the most important elements to obtain an overview and information on activities at all levels of program implementers.The purpose of this study was to describe the completeness of filling out the leprosy patient cards at the Pekalongan City Health Center. The method of this type of qualitative descriptive research by determining the sources using purposive sampling technique totaling 5 leprosy officers and 33 leprosy patient cards. Data collection using in-depth interviews and observations. Data analysis used qualitative analysis with the stages of data collection, data reduction, data presentation, drawing conclusions and verification. Result : overall of the 33 cards, the average completeness of the leprosy card filling out was 75%. The incompleteness of filling out leprosy patient cards is due to the lack of attitude of leprosy officers, the lack of completeness checks by superiors and limited human resources. Based on the results of the research, it is suggested that the Pekalongan City Health Office be able to coordinate the cooperation between leprosy officers in all puskesmas in Pekalongan City to make joint visits in turn so that the household contact and environmental contacts can be filled completely and increase supervision of the completeness of filling out leprosy patients cards.